60.5k views
5 votes
Find the general solution of the equation: (y^2-2xy)dx + (2xy-x^2)dy = 0

1 Answer

2 votes

The ODE is exact, since


(\partial(y^2-2xy))/(\partial y)=2y-2x


(\partial(2xy-x^2))/(\partial x)=2y-2x

so there is solution
f(x,y)=C such that


(\partial f)/(\partial x)=y^2-2xy


(\partial f)/(\partial y)=2xy-x^2

Integrating both sides of the first PDE wrt
x gives


f(x,y)=xy^2-x^2y+g(y)

Differentiating both sides wrt
y gives


(\partial f)/(\partial y)=2xy-x^2+(\mathrm dg)/(\mathrm dy)=2xy-x^2


\implies(\mathrm dg)/(\mathrm dy)=0\implies g(y)=C

Then the solution to the ODE is


f(x,y)=\boxed{xy^2-x^2y=C}

# # #

Alternatively, we can see that the ODE is homogeneous, since replacing
x\to tx and
y\to ty reduces to the same ODE:


((ty)^2-2(tx)(ty))\,\mathrm d(tx)+(2(tx)(ty)-(tx)^2)\,\mathrm d(ty)=0


t^3(y^2-2xy)\,\mathrm dx+t^3(2xy-x^2)\,\mathrm dy=0


(y^2-2xy)\,\mathrm dx+(2xy-x^2)\,\mathrm dy=0

This tells us we can solve by substituting
y(x)=xv(x), so that
\mathrm dy(x)=x\,\mathrm dv(x)+v(x)\,\mathrm dx, and the ODE becomes


(x^2v^2-2x^2v)\,\mathrm dx+(2x^2v-x^2)(x\,\mathrm dv+v\,\mathrm dx)=0


v(v-2)\,\mathrm dx+(2v-1)(x\,\mathrm dv+v\,\mathrm dx)=0


3v(v-1)\,\mathrm dx+x(2v-1)\,\mathrm dv=0

which is separable as


(1-2v)/(3v(v-1))\,\mathrm dv=\frac{\mathrm dx}x

Integrating both sides gives


-\frac13\ln|v(1-v)|=\ln|x|+C


v(1-v)=\frac C{x^3}

and solving in terms of
y(x),


\frac yx\left(1-\frac yx\right)=\frac C{x^3}


xy(x-y)=C


\boxed{x^2y-xy^2=C}

User Diminuta
by
5.0k points